Increasing the defense potential of firearm owners in the face of a military threat in Poland - Waldemar Kaak; Joanna Olszewska (Defence Science Review, 2021)
Objectives: The aim of this work is to determine the defense potential represented by firearm owners in Poland in relation to the Armed Forces of the Republic of Poland, in particular the number of weapon units that can be used in the face of a possible armed attack.